The Influence of Financing on the Loan to Deposit Ratio (LDR) in Baitul Maal Wat Tamwil in Bandung - Meilani Nur; Dayyinah Ayunda Rahmawati (Wasīlah: Journal Of Sharia Sciences, 2025)
This study aims to analyze the impact of financing on the Loan to Deposit Ratio (LDR) in BMT (Baitul Maal Wat Tamwil) financial institutions in Bandung. Understanding this relationship is crucial, as the LDR serves as a key indicator of liquidity management and financial stability within Islamic microfinance institutions like BMT. The research population includes all financial reports, particularly balance sheet reports, from BMT financial institutions operating in Bandung City. A sample was taken from financial reports covering the period from 2015 to 2023. The collected data was processed using the LDR (Loan to Deposit Ratio) formula and analyzed through various statistical methods using SPSS 24, including simple linear regression analysis, correlation analysis, and the t-test, to assess the significance and strength of the relationship between financing and LDR. The findings of the study indicate that financing does not have a significant effect on the LDR of BMT institutions in Bandung City. This suggests that LDR is influenced by multiple factors beyond financing alone. Other key determinants include third-party funds, the level of deposits, and the equity owned by BMT institutions, which play a crucial role in shaping liquidity ratios. These findings highlight the complexity of liquidity management in Islamic financial institutions and suggest that a more comprehensive approach is needed to evaluate the factors affecting LDR.